AP2/ERF genes associated with superfast fig (Ficus carica L.) fruit ripening - Cui, Yuanyuan; Zhai, Yanlei; He, Jiajun; Song, Miaoyu; Flaishman, Moshe A.; Ma, Huiqin (Frontiers in Plant Science, 2022)
Fig fruits have significant health value and are culturally important. Under suitable climatic conditions, fig fruits undergo a superfast ripening process, nearly doubling in size, weight, and sugar content over three days in parallel with a sharp decrease in firmness. In this study, 119 FcAP2/ERF genes were identified in the fig genome, namely 95 ERFs, 20 AP2s, three RAVs, and one soloist. Most of the ERF subfamily members (76) contained no introns, whereas the majority of the AP2 subfamily members had at least two introns each. Three previously published transcriptome datasets were mined to discover expression patterns, encompassing the fruit peel and flesh of the ‘Purple Peel’ cultivar at six developmental stages; the fruit receptacle and flesh of the ‘Brown Turkey’ cultivar after ethephon treatment; and the receptacle and flesh of parthenocarpic and pollinated fruits of the ‘Brown Turkey’ cultivar. Eighty-three FcAP2/ERFs (68 ERFs, 13 AP2s, one RAV, and one soloist) were expressed in the combined transcriptome dataset. Most FcAP2/ERFs were significantly downregulated (|log2(fold change) | ≥ 1 and p-adjust < 0.05) during both normal fruit development and ethephon-induced accelerated ripening, suggesting a repressive role of these genes in fruit ripening. Five significantly downregulated ERFs also had repression domains in the C-terminal. Seven FcAP2/ERFs were identified as differentially expressed during ripening in all three transcriptome datasets. These genes were strong candidates for future functional genetic studies to elucidate the major FcAP2/ERF regulators of the superfast fig fruit ripening process.